Serial Image Learning Media to Improve Fourth Grade Elementary School Students' Narrative Writing Skills - Wijayasir, Urie Elmara; Astuti, Tri (Journal of Education Reseach and Evaluation, 2025)
Many children still have difficulty developing their creative ideas through effective writing and sentences. This study aims to develop a series of picture learning media that can improve students' narrative writing skills. This study uses the Research and Development method with the ADDIE model. The subjects of the study were 29 fourth-grade students. Validation of the series of picture-learning media was carried out by one media expert and one material expert. Data collection methods used in this study include observation, interviews, tests, questionnaires and documentation. The instruments used in collecting data were questionnaire sheets and test questions. The techniques used in analyzing data were qualitative, quantitative, and inferential statistical descriptive analysis. This study's results indicate that using a series of picture media is quite effective in improving students' writing skills. This is indicated by the results of the small group N-gain score of 0.6349 and the N-gain results of 0.6191. The results of the media expert validation obtained 93.75% with the category "Very Eligible", and the results of the material expert validation obtained 92.5% with the category "Very Eligible". The teacher's response was 92.5%, the response of students in small groups was 89.6%, and the response of students in large groups was 88%. It was concluded that the serial picture learning media is suitable for use as a learning medium to improve the narrative writing skills of grade IV elementary school students.